Pirólise do pireno sob pressão com nitrogênio em temperaturas moderadas - Vassem, Gilceia Libera Sarnaglia (2008)
We made an study to help the understanding of the formation process ofpitches using a homogeneous compound, pyrene,whichis a polycyclic aromatic hydrocarbon constituted byfour benzene rings,meltingpointbetween145 and148 °C anda boilingpoint of 404 °C. The pyrene wassubmitted toheat treatmentsunder nitrogen atmospherein an experimentalset updeveloped at the Laboratory of Carbon MaterialsoftheFederal University of Espírito Santo. The heat treatments were performed at 400, 450 and 500 °C, with residence timeof 0, 1, 2, 4, 8 and 16 hours, under a final pressureof 6,9 MPa. The samples were characterized bythermogravimetry, differential scanning calorimetry, X-ray diffraction, solid-state 13C nuclear magnetic resonance spectroscopy,and scanning electron microscopy. We did not observe significant modifications of the samples heat treated at 400 and 450 °Cfor all studied residence times in relation to the original precursor. The samplesobtained at 500 °C suffered significant modifications from 4 hoursof residue time; the treatments for8 h and 16 h produced segregation, the samplesbeingdivided into two well-defined regions (A and B regions). The 500-8hBand 500-16hBsamples sufferedthe mostnoticeablemodifications in relation to the precursor. Theelementalanalysis and thermogravimetric results indicatedthat the 500-8hBsamplepresentedcharacteristics similar topitches, additionalstudieswillbenecessarytoverifyiftheanisotropiccarbonmaterialisreallyapitch. The elementalanalysis, X-ray diffraction and scanning electron microscopy resultsindicatedthat the 500-16hBsample presentedcharacteristicsof acoke. The X-ray diffraction patternsand NMR spectraresults of the 500-16hBsample indicate the formation of aromatic lamellae typicalof the turbostratic structure of grafitizable carbon materialswith a relatively hight value of Lcobtained at a low heat treatment temperature.